Identifying Olfactory Phenotypes to Differentiate Between COVID‐19 Olfactory Dysfunction and Sinonasal Inflammatory Disease. (15th March 2022) - Somani, Shaan N.; Farrokhian, Nathan; Macke, Jamison; Yu, Katherine M.; Uhlich, Cody; Rea, Emma L.; Villwock, Jennifer A.
Abstract : The objective of this study was to identify specific olfactory phenotypes—patterns of olfactory performance—across distinct cohorts with or without olfactory dysfunction (OD). Adult patients underwent testing via a novel olfactory testing methodology in 1 of 4 groups based on health status: sinonasal inflammatory condition (chronic rhinosinusitis or allergic rhinitis), ≥4 weeks of self‐reported OD after resolved COVID‐19 infection, Alzheimer's disease, and healthy control. Participants' scores for each scent were normalized on a scale of 0 to 1 relative to their worst and best scores. Agglomerative hierarchal cluster analysis was performed on normalized data for the COVID‐19 and sinonasal cohorts. Resulting clusters from the penultimate merger revealed a sensitivity of 81% and specificity of 63% for the detection of patients with COVID‐19. These results support that there are olfactory phenotypes that may discriminate COVID‐19 OD from sinonasal inflammatory disease. These phenotypes will likely become increasingly leveraged in the workup and treatment of patients with OD.